The genus Peckoltia with the description of two new species and a reanalysis of the phylogeny of the genera of the Hypostominae (Siluriformes: Loricariidae) - Armbruster, Jonathan W. (Zootaxa, 2008)
Peckoltia contains 12 described species, eight of which are considered valid. Peckoltia arenaria, P. filicaudata, and P. ucayalensis are recognized as synonyms of P. bachi and P. kuhlmanni is recognized as a synonym of P. vittata. In addition, two new species are described. The type species of Peckoltichthys and Sophiancistrus are synonyms of P. bachi and both genera are recognized as junior synonyms of Peckoltia. The species of Peckoltia range throughout much of the Amazon basin, the upper Orinoco, the upper Essequibo, and perhaps the Maroni, and can be identified from most other ancistrins by having dentaries that form angle of 90° or less and from others with angled dentaries by lacking the synapomorphies of those genera. The species of Peckoltia vary from one another mostly in coloration. Peckoltia braueri, P. caenosa n. sp., P. cavatica and P. vittata lack spots on the head while the other species have them. Peckoltia braueri and P. cavatica have orange bands in the dorsal and caudal fins and have the bones and plates of the head and nape outlined in black (vs. no orange bands and head plates and bones not outlined in black in P. caenosa and P. vittata). Peckoltia caenosa has a color pattern consisting of dark vermiculations on the head and abdomen (vs. saddles or blotches on the head and faint dark spots on the abdomen in P. vittata). Among the species with spots on the head, P. lineola n. sp. and P. vermiculata have some of the spots combining to form vermiculations (vs. spots free in P. bachi, P. brevis, P. furcata, and P.oligospila) with the vermiculations larger than the pupil in P. lineola and narrower in P. vermiculata and the vermiculations radiating from a central point in P. vermiculata vs. no such pattern in P. lineola. Peckoltia bachi can be identified from the other species by having widened pelvic-fin spines that can be pulled ventrally such that they are completely ventral and parallel to the body (vs. pelvic-fin spines narrow and cannot be adducted ventral to body) and by having the eye low on the head (vs. high). Peckoltia brevis can be identified from P. furcata and P. oligospila by having well-developed dorsal saddles (vs. saddles faint), no spots on the body behind the nape (vs. spots generally present behind the nape); from P. oligospila by having bands in the caudal fin (vs. spots); and from P. furcata by having the lower caudal-fin spine longer than the upper (vs. upper spine longer). Peckoltia furcata can be identified from P. oligospila by having the upper caudal-fin spine longer than the lower (vs. lower spine longer) and by having bands in the caudal fin (vs. spots). Ancistrus yaravi had been recognized as a species of Peckoltia. The type of A. yaravi is lost, but the original description suggests that the species is the senior synonym of Neblinichthys roraima. A revised morphological phylogeny demonstrates the lack of support for Peckoltia and Hemiancistrus as monophyletic, and phenetic definitions are provided for the two genera. The phylogeny also demonstrates a lack of support of the genus Watawata.